Development of the optimization model of production and delivery plans taking into account uncertainty factors - Куруджи, Юлия Владимировна (Eastern-European Journal of Enterprise Technologies, 2015)
A static model of joint optimization of the enterprise production plan and the delivery plan of finished products to a given set of consumers was developed and investigated in the paper. The model takes into account the random fluctuations of the line speed and demand for products. The developed model describes the supply chain, considering the risk factors. The required control parameters are the production volume of several types of products and volumes of transportation. The model is based on the known deterministic model of the production-transportation problem of linear programming. As a result, the production-transportation type single-stage stochastic optimization problem was obtained, and its deterministic equivalent was built. The latter is a complex problem of nonconvex nonlinear programming, to solve which the first and second order optimization techniques are used. The model constructed using the appropriate software can be used in the practice of logistics managers. The results are the basis for further research and synthesis, for example, for building dynamic models of inventory management, taking into account internal and external uncertainty factors.